Pelaksanaan Ganti Rugi Akibat Pembebasan Hak Atas Tanah Menurut Undang-Undang No. 2 Tahun 2012 Tentang Pengadaan Tanah bagi Kepentingan Umum - Evangelista, Beverly; Febriana, Asyri (Lembaga Yasin AlSys, 2023)
The authority of the State in the acquisition of land rights for the public interest in Indonesia is derived from the State's Right to Control. Because of that, on the basis of that authority, the state has the right to take over citizens' land with the provision of providing proper compensation. To provide legality for this authority, the State issued Law of the Republic of Indonesia Number 2 of 2012 concerning Land Procurement for Public Interests. Implementation of Forms of Compensation according to Law no. 2 of 2012 concerning Land Acquisition for Development for the Public Interest, clearly states that Compensation is a proper and fair compensation to the entitled party in the land acquisition process. Assessment of the value of Compensation is carried out plot per plot of land, including: land, above-ground and underground space, buildings, plants, objects related to land, and other losses that can be assessed. Based on the assessment of the amount of Compensation, the provision of Compensation can be given in the form of: money, replacement land, resettlement, share ownership and other forms.